SARS-CoV-2 remains infectious for at least a month on artificially-contaminated frozen berries. (October 2022) - Esseili, Malak A.; Mann, Amy; Narwankar, Revati; Kassem, Issmat I.; Diez-Gonzalez, Francisco; Hogan, Robert J.
Abstract: The potential transmission of SARS-CoV-2 via food has been controversial since the beginning of the COVID-19 pandemic. To investigate these concerns, reliable detection methods and data on virus die-off rates in various foods are needed. Here, an FDA-standard method for the detection of enteric viruses' RNA from soft fruits was modified for the recovery of infectious SARS-CoV-2. Then, the survival of SARS-CoV-2 on berries was investigated as well as the effectiveness of washing virus-contaminated berries with water. The modified method did not significantly reduced log infectivity titers of recovered viruses, but berries did. The detection limit of the method for infectious SARS-CoV-2 was ∼2.97 log TCID50/g of berries. On SARS-CoV-2-inoculated berries that were stored at 4 °C for 7 days, significant reductions in SARS-CoV-2 infectivity were observed over time. In contrast, on frozen berries, infectious SARS-CoV-2 was recovered for 28 days without significant reductions. Washing SARS-CoV-2-inoculated berries with water removed >90% of infectious viruses within 10 min; however, infectious viruses were detected in wash water. Therefore, on fresh berries infectious viruses are markedly inactivated over time and can be largely removed by washing with water. However, the prolonged survival of SARS-CoV-2 on frozen berries suggests that the virus can potentially spread through frozen fruits. Highlights: SARS-CoV-2 remains infectious on frozen berries for at least a month. SARS-CoV-2 contamination of fresh berries can be mitigated by storage at 4 °C. Washing berries in water can significantly reduce SARS-CoV-2 contamination by >90%. An FDA standard method can be adapted to detect infectious SARS-CoV-2 on berries.